The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3892/ijmm.2019.4313
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of glucose metabolism associated genes in a tacrolimus‑induced post‑transplantation diabetes mellitus in rat model

Abstract: Post-transplantation diabetes mellitus (PTdM) is a known side effect in transplant recipients administered with immunosuppressant drugs, such as tacrolimus (Tac). Although injury of islet cells is considered a major reason for Tac-induced PTdM, the involvement of insulin resistance in PTdM remains unknown. In the present study, expression levels of adipocytokines, glucose metabolism associated genes and peroxisome proliferator-activated receptor (PPAR)-γ in adipose, muscular and liver tissues from a rat model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…TAC induced weight loss was common in the diabetic model, and vancomycin did not reverse it here. 42 , 43 No discernible differences in fasting glucose levels were observed among the three groups ( Figure 1b ). A set of tests was performed to assess the effects of TAC on glucose homeostasis and insulin sensitivity.…”
Section: Resultsmentioning
confidence: 91%
“…TAC induced weight loss was common in the diabetic model, and vancomycin did not reverse it here. 42 , 43 No discernible differences in fasting glucose levels were observed among the three groups ( Figure 1b ). A set of tests was performed to assess the effects of TAC on glucose homeostasis and insulin sensitivity.…”
Section: Resultsmentioning
confidence: 91%
“…Ling et al 18 demonstrated that tacrolimus directly (insulin signaling pathway) and indirectly (hepatic steatosis) leads to hepatic insulin resistance; another study revealed that adipocytokines and Peroxisome Proliferator-Activated Receptor Gamma signaling serve important roles in the pathogenesis of tacrolimus-induced insulin resistance. 19 Considering these effects of calcineurin inhibitors on insulin resistance, it may be reasonable to reduce the dosage of calcineurin inhibitors and to supplement with other immunosuppressants such as mammalian target of rapamycin inhibitors. Also, the changes in MI and HOMA-IR after pancreas transplantation may be affected by the surgical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that quadriceps are kinds of oxidative muscle which were closely related to insulin resistance [20] while the muscle fiber types of gastrocnemius are glycolytic type [20]. Our preliminary study had shown peroxisome proliferator-activated receptor-(PPAR-) γ which was related to insulin resistance in Tac-induced PTDM expressed in quadriceps [21]. So, quadriceps and gastrocnemius were dissected from the PTMD model induced by Tac to test this hypothesis.…”
Section: Introductionmentioning
confidence: 88%